Good Company Governance And Risk Management On Company Value With Bank Performance - Jefry Gasperz; Christina Sososutiksno; Franco Benony Limba (Jurnal Akuntansi, 2022)
Economics movements either real sector or monetary sector undergo dynamic development and affect the economy banking sector. This study aims to elucidate bank performance preceding and proceeding the administration of regulation of Financial Service Authority and distinctive evaluation between GCG and risk management. This study is an approach used to observe all demands and information related to corporation values (Banks) which can be completely prepared by policy makers. Explanative survey with structural equation modeling analysis is employed. Research samples are state, foreign, and private banks which are accessible from Bank Indonesia (BI) website, 2010 – 2018 period. GCG and Risk Management have a positive effect on company value, while bank performance has a negative effect on company value. GCG has a negative effect on bank performance while risk management has a positive effect on bank performance. The roles of Financial Service Authority influence the average mechanism value of GCG and risk management, meanwhile bank performance and company’s values have no effects when compared with beforehand and afterward the formation of Financial Service Authority.